Employee Self Service-based Human Resources Information System Development and Implementation. Case Study: BCP Indonesia - Lestari Margatama (Jurnal Informatika, 2017)
Human Resources Information System is a Decision Support System that provides necessary information regarding human resources in an organization. Web-based e-HR is one of the best practical solution in human resources management that allows employees to focus more on their job instead of HR administration procedures. By implementing Employee Self Service (ESS) it is expected that worker satisfaction can be improved and in turn will also improve employees’ performance. The web-based ESS is characterized by personalized information approach which offers personal and management services on information access and structured workflow process. The object covered in this research is HR administration of PT. BCP to create and implement ESS with system prototype development and UML modeling tool. The resulting system is designed to quickly access the information and company procedures to shorten the time for BCP’s employee administration and documentation